Ordenanzas públicas con enfoque participativo y su incidencia en la soberanía y seguridad alimentaria del cantón Quevedo año 2021 - Mora Bustos, Ingrid María (2022)
Food Sovereignty and Security are relevant in the world, when countries apply a public ordinance through their decentralized autonomous governments. These legal norms seek to guarantee food self-sufficiency through local production. Evaluate the incidence of a public ordinance on food sovereignty and security and its implications, both in child malnutrition, as well as in youth and adult malnutrition and in fair trade for farmers in the sector. An investigation in the field is contemplated through surveys and interviews for the collection of information. Improvements in the quality of life of the citizens of Quevedo, and growth in the level of production and marketing of farmers are contemplated. It culminates with the results where the lack of economic resources generates lack and little variety of food; traditionally people buy in neighborhood stores; with the absence of agricultural fairs that can be used by farmers who are in a position to produce and supply a variety of quality food products at competitive prices.